Dental Anxiety Among Students of the University of Rijeka, Croatia - Nataša Ivančić Jokic; Laura Matičić; Marija Šimunović Erpušina; Dorotea Petrović; Odri Cicvarić; Danko Bakarčić (University of Zagreb. School of Dental Medicine, 2024)
Objectives: Dental anxiety is a common problem and a great challenge for many patients, but also for dentists - the treatment of anxious patients is considered to be one of the most stressful situations for dentists. The aim of this study was to evaluate the prevalence of dental anxiety among the students of the University of Rijeka and to detect possible differences in the level of anxiety among students of different study programs. Participants and methods: This cross-sectional study included 290 students from different faculties of the University of Rijeka (Faculty of Law, Faculty of Humanities and Social Sciences, Faculty of Engineering, Faculty of Medicine, Faculty of Dental Medicine), 73 (25.17%) male and 217 (74.83%) female students. The study was conducted online via The Modified Dental Anxiety Scale (MDAS) in 2020 and sampling was based on voluntary responses. The Student's t-test and ANOVA were used to compare differences in MDAS scores among students. Results: There is a significant difference in dental anxiety levels between students from the Faculty of Humanities and Social Sciences and Faculty of Dental Medicine (MDAS=11.32±4.11, MDAS=8.84±3.03, p=0.01), and also between students from the Faculty of Law and Faculty of Dental Medicine (MDAS=11.47±4.64, MDAS=8.84±3.03, p <0.01). Conclusions: This research showed that non-dental students have a higher level of dental anxiety than dental students. Sufficient knowledge of dental and oral health could potentially overcome dental fear and anxiety. Therefore, there is a need to provide additional dental education throughout the university curriculum.